Host–guest interactions in nor-seco-cucurbit[10]uril: novel guest-dependent molecular recognition and stereoisomerism - Zhang, Xiaodong; Wu, Wei; Tao, Zhu; Ni, Xin-Long (Beilstein Journal of Organic Chemistry, 2019)
The unique monomer and excimer fluorescence emissions of pyrene were first exploited as distinctly photophysical signals to identify the possible diastereomers of guests within nor-seco-cucurbit[10]uril (NS-CB[10]) cavities. Further experiments revealed that balancing the hydrophilic and hydrophobic effects of the guest in aqueous solution can improve the molecular recognition and binding ability of NS-CB[10].
Keywords: fluorescent; host–guest interaction; macrocycles; molecular recognition; nor-seco-cucurbit[10]uril; pyrene